2020
DOI: 10.1108/ijmf-04-2019-0129
|View full text |Cite
|
Sign up to set email alerts
|

Managerial optimism and corporate cash holdings

Abstract: PurposeThis paper examines the effects of managerial optimism on corporate cash holdings.Design/methodology/approachThe authors construct a novel measure of managerial optimism based on the linguistic tone of annual reports by applying a Naïve Bayesian Machine Learning algorithm to non-numeric parts of Vietnamese listed firms' reports from 2010 to 2016. The paper employs firm and year fixed effects model and also uses the generalized method of moments estimation as robustness checks.FindingsThe authors find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
(123 reference statements)
0
8
0
Order By: Relevance
“…According to the overinvestment hypothesis, optimism simply increases cash holding on firm value, because higher cash holding intensifies the overinvestment by investing in value-destroying projects. Tran et al (2020) recently revealed that optimistic managers seek external financing but despite its cost they are adamant that such problems are overcome by value-generating projects. Consistent with these arguments, Malmendier et al (2007) noted that optimists overestimate project cash flows and want to invest more with available adequate cash holding and external finance.…”
Section: Managerial Optimism and Cash Holdingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the overinvestment hypothesis, optimism simply increases cash holding on firm value, because higher cash holding intensifies the overinvestment by investing in value-destroying projects. Tran et al (2020) recently revealed that optimistic managers seek external financing but despite its cost they are adamant that such problems are overcome by value-generating projects. Consistent with these arguments, Malmendier et al (2007) noted that optimists overestimate project cash flows and want to invest more with available adequate cash holding and external finance.…”
Section: Managerial Optimism and Cash Holdingmentioning
confidence: 99%
“…Optimistic managers are always forecasting positive outcomes and better future performance. They are confident and presume that under their direction all the required work will be accomplished and generate a superior return than the actual return (Tran et al 2020). Optimists are convinced that overestimating the return of well-performed firms is justified and assume that the market undervalues their securities.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent stream of research is trying to shed light on the impact of managerial characteristics on cash holdings. Tran et al (2021) examined the impacts of managerial optimism on corporate cash holdings. Their study revealed that that firms managed by optimistic managers had higher cash holdings than firms managed by non-optimistic managers.…”
Section: Corporate Cash Holdings and National Culturementioning
confidence: 99%
“…Under the overinvestment hypothesis, optimism enhances the negative effect of cash holding on firm value because higher cash holding intensifies the overinvestment by investing in valuedecreasing projects. Further, Tran, Tu, and Hoang (2020) revealed that optimist managers seek external financing is costly and expect it can reduce shortly by value-generating projects. Consistent with these arguments, Malmendier, Tate, and Yan (2007) noted that optimists overestimate the project cash flows and excite to invest more with the availability of adequate cash holding and opportunity to finance externally.…”
Section: Managerial Optimism and Cash Holdingmentioning
confidence: 99%
“…Optimist managers are always forecasting positive outcomes and expect better future performance. Optimist managers are confident and presume that assignments under their direction are accomplished well in time and generate a superior return than the actual return (Tran, Tu, and Hoang 2020). Optimists are convinced to overestimate the return of wellperformed firms and assume that the market undervalues their securities.…”
Section: Introductionmentioning
confidence: 99%